Assessing the State of Modern Physics Education: Pre-test Findings and Influencing Factors - Tene, Talia; Bodero-Poveda, Elba; Vique López, Diego; Vacacela Gomez, Cristian; Bellucci, Stefano (Emerging Science Journal, 2024)
Technology and our conceptions of reality have both been significantly impacted by modern physics. However, due to a variety of issues, such as disparities in educational resources, differing emphasis on science education, cultural attitudes, and language obstacles, students in Latin America, including Ecuador, have a limited understanding of modern physics. The present work exposes a pre-test methodology to evaluate students' knowledge and pinpoint their areas of weakness. The analysis of the results indicates that most students received lower grades, while a smaller proportion obtained higher scores. Our findings reveal significant knowledge gaps, misconceptions, and uncertainty among the participants regarding various topics related to the constituent and stability of the nucleus, quantum behavior, nuclear models, radioactive decay, and natural radioactive sources. Additionally, it was statistically demonstrated (Kruskal-Wallis H test) that misconceptions, uncertainties, and knowledge gaps are not significantly related to learning styles. The type of college substantially impacts academics, with private university students typically receiving higher grades. These results offer insightful information about student performance, how learning styles and college types affect academic achievement in modern physics, and the effects of living area and academic level. Doi: 10.28991/ESJ-2024-SIED1-01 Full Text: PDF